2015
DOI: 10.1371/journal.pone.0136325
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Socializing Propensity

Abstract: Using large-scale interaction data from a virtual world, we show that people’s propensity to socialize (forming new social connections) varies by hour of the day. We arrive at our results by longitudinally tracking people’s friend-adding activities in a virtual world. Specifically, we find that people are most likely to socialize during the evening, at approximately 8 p.m. and 12 a.m., and are least likely to do so in the morning, at approximately 8 a.m. Such patterns prevail on weekdays and weekends and are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The key strengths of this study are the clear weekly and diurnal rhythms revealed simply using the timing of postings of Reddit data. No pre-processing steps were required, nor did the semantic content of the posts have to be analysed for these to be recognised as strong signals, similar to those observed for socialising propensity using online gaming data, which showed the highest probability of making social connections at night (between 20:00 h and midnight) [34].…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…The key strengths of this study are the clear weekly and diurnal rhythms revealed simply using the timing of postings of Reddit data. No pre-processing steps were required, nor did the semantic content of the posts have to be analysed for these to be recognised as strong signals, similar to those observed for socialising propensity using online gaming data, which showed the highest probability of making social connections at night (between 20:00 h and midnight) [34].…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…Social behavior in everyday life might follow a systematic pattern or rhythm (e.g., people may more often be with strangers on their evening commute and with family at night rather than the other way around; Zhang et al, 2015). Similarly, happiness might follow a natural rhythm (e.g., people typically feel happier after lunch than before lunch; Golder & Macy, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…De Zeeuw et al ( 2018), García et al (2012), Manly et al (2002), May and Hasher (1998), Ramírez et al (2012), Song et al (2018), andWest et al (2002) Circadian variations in the ability to suppress judgmental heuristics and stereotypic biases Bodenhausen (1990) and Zadra and Proffitt (2014) Circadian variations in socializing behaviors Hasler et al (2008) and Zhang et al (2015) Circadian variations in morality and ethical behavior Gunia et al (2014) and Later chronotypes demonstrate lower levels of emotional control and higher levels of dysfunctional impulsivity , Antúnez et al (2014), Caci et al (2004), Caci et al (2005), Hwang et al (2016), Kang et al (2015), Neubauer (1992), Ottoni et al (2012), Park et al (2015), Russo et al (2012), Schlarb et al (2014), and Wilson (1990) Change oriented (envisioning, creativity, innovativeness, risktaking, novelty seeking, and entrepreneurial)…”
Section: Leadership Activitiesmentioning
confidence: 99%